Pengaruh Model Problem Based Learning Dipadukan Dengan Tipe Teams Game Tournament Untuk Meningkatkan Berpikir Kritis Siswa Kelas XI di MAL UINSU - Kirana, Hafsah Nanda; Rohani (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine the effect of integrating the Problem Based Learning (PBL) model with the Teams Game Tournament (TGT) type on improving students’ critical thinking skills. The research employed a quantitative approach with a quasi-experimental method using a Pretest-Posttest Control Group Design. The population consisted of 61 students, divided into class XI IPA-1 (30 students) and class XI IPA-3 (31 students), selected through cluster random sampling. Data analysis showed that the Shapiro-Wilk normality test resulted in significance values of 0.085 (pretest) and 0.405 (posttest), both greater than 0.05, indicating that the data were normally distributed. The homogeneity test using Levene’s statistic yielded a significance value of 0.718 > 0.05, confirming equal variances. Hypothesis testing produced a significance value of 0.000 < 0.05, leading to the rejection of H0 and acceptance of Ha. Therefore, it can be concluded that the application of the Problem Based Learning model combined with the Teams Game Tournament type has a significant positive effect on enhancing the critical thinking skills of class XI students at MAL UINSU in the digestive system topic.